2022
DOI: 10.12740/pp/onlinefirst/122461
|View full text |Cite
|
Sign up to set email alerts
|

Comparative assessment of the relationship between emotional factors and quality of life in a group of patients with type 1 and type 2 diabetes – preliminary report

Abstract: Cel pracyStały wzrost zachorowań na cukrzycę skłania do poszukiwań nowszych form leczenia, ale także do badań różnych czynników mających wpływ na jakość życia tych pacjentów. Celem pracy była ocena związku wybranych parametrów stanu psychicznego z jakością życia pacjentów z cukrzycą.MetodaBadaniem objęto 51 pacjentów z cukrzycą typu 1 i 52 pacjentów z cukrzycą typu 2. W badaniach wykorzystano skale: jakości życia SF-36, AIS, HADS oraz SWLS.WynikiPacjenci z cukrzycą typu 2 osiągnęli niższe wartości niż pacjenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
2
2
0
Order By: Relevance
“…The present study has shown that the longer duration of the disease is negatively correlated with the metabolic control in the group of patients with diabetes. Similar conclusions were formulated by Badura-Brzoza et al [17]. These relationships may also be explained by the burnout syndrome associated with reluctance to control glycemia appearing several years after the onset of the disease [24].…”
Section: Glycated Hemoglobin Level In Relation To Socio-demographic V...supporting
confidence: 81%
See 2 more Smart Citations
“…The present study has shown that the longer duration of the disease is negatively correlated with the metabolic control in the group of patients with diabetes. Similar conclusions were formulated by Badura-Brzoza et al [17]. These relationships may also be explained by the burnout syndrome associated with reluctance to control glycemia appearing several years after the onset of the disease [24].…”
Section: Glycated Hemoglobin Level In Relation To Socio-demographic V...supporting
confidence: 81%
“…In the analyzed studies, there was no correlation between the SWLS scores and the duration of the disease, but a significant correlation was found between SWLS and the age of the respondents: the older the patients, the greater the percentage of declared life satisfaction. As reported by some researchers, the longer duration of the disease was negatively correlated with the assessment of life satisfaction [17,20,21]. In the present study, no significant relationship was found between the duration of diabetes and life satisfaction.…”
Section: Life Satisfaction Level In Relation To Socio-demographic Var...supporting
confidence: 52%
See 1 more Smart Citation
“…Diabetes is a chronic disease that requires ongoing medical management to reduce the risk of acute and chronic complications and improve QoL [ 47 , 48 ]. However, patients with diabetes may be deeply affected by poor blood sugar control, long-term diet and drug control symptoms, and a variety of complications of physical damage, so that patients feel physically and mentally exhausted, QoL seriously decreased, easy to cause negative emotions [ 49 51 ]. A study has shown that PR is an important predictor of QoL, reducing anxiety and depression and enabling individuals to achieve a higher QoL [ 52 ].…”
Section: Discussionmentioning
confidence: 99%